2014
DOI: 10.5137/1019-5149.jtn.10942-14.0
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the sacral canal and hiatus using multidetector computed tomography for interventional procedures

Abstract: AIm:The sacral canal has been frequently used as "a passage" for minimally invasive diagnostic and therapeutic procedures for spinal diseases. The aim of the present study was to investigate morphometric analyses of the sacral canal, hiatus, and surrounding structures according to different age groups and gender by using the "multidetector computed tomography" method. mATeRIAL and meTHods: Multiplanar-reconstructed images from 300 adult (150 females and 150 males, between 20 and 80 years old) were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…In MDCT studies, the mean value of APCWHSA was similar in men and women, and it was higher in men in studies conducted with USG. In studies conducted in MDCT, the mean value of male and female ICD was found to be lower than in studies performed with USG [39][40][41].…”
Section: Discussioncontrasting
confidence: 63%
“…In MDCT studies, the mean value of APCWHSA was similar in men and women, and it was higher in men in studies conducted with USG. In studies conducted in MDCT, the mean value of male and female ICD was found to be lower than in studies performed with USG [39][40][41].…”
Section: Discussioncontrasting
confidence: 63%
“…The authors suggested that sacral cornua are inadequate as a bony landmark and thus cannot be utilised in CEB in 21.5-50% of the population. Furthermore, in a research study of 300 multidetector computed tomography (MDCT) images, bilateral plane cornua were found in 3%, unilateral plane cornua in 5%, bilateral short cornua in 7%, and unilateral short cornua in 15.3% [52]. In addition, sacral cornua were examined through three-dimensional computed tomography (3D CT) images in children and they were bilaterally absent in 3.5% and unilaterally absent in 4.2% [53].…”
Section: Variations In the Morphology Of Sacral Cornua (Horns)mentioning
confidence: 99%
“…In the remaining 15 cases with a needle distance over 6 cm, only six cases had a vertebral canal that was mildly curved, requiring that we obtain this needle distance by joining two straight lines at a slight angle (5° to 30°) off a straight path, along the lumen of the caudal epidural space. Riascos et al (2011) and Kilicaslan et al (2015) previously recorded similar average angulations within the vertebral canal on CT scans.…”
Section: Resultsmentioning
confidence: 62%
“…Riascos et al (2011) andKilicaslan et al (2015) previously recorded similar average angulations within the vertebral canal on CT scans.4 | DISCUSSION4.1 | Anatomy and morphology of the sacrum and vertebral canal contents relevant to a trans-sacral hiatus approach…”
mentioning
confidence: 86%